Unlocking Tibro: reimagining collaboration and transformation in rurban areas - GABRIELSSON, LINNÉA; PETERSON, SOFIA (My University, 2023)
The purpose of this master’s thesis is to challenge the status quo of rurban development since there is frequently a lack of visions for how rurban areas can develop in novel ways. The project takes place in Tibro, Sweden, and focuses on the former train track area and its old stock building known as Centralföreningen. The thesis presents a method for how one can approach renovation projects in rurban areas by using speculative scenarios. Therefore, three alternative futures are suggested and set within the building based on information obtained from the municipality’s comprehensive plan and interviews with officials as well as associations. The visions highlight citizen collaboration and association life, as well as current challenges existing in Tibro today, including unemployment, a lack of engagement from youths and a distance between the municipality and the citizens. The futures are visualised as spatial proposals within Centralföreningen and investigate its potential as a social platform to strengthen the community. As a result, the design process serves as a tool for research and further discussion of the overall goal: How can a method based on new values and forms of collaborations help transform Centralföreningen and strengthen Tibro? The concepts based on the scenarios are summarised and visualised into one final proposal that demonstrates the potential of Centralföreningen. A large focus of the thesis is social value-making, the creation of new meeting spaces as well as responsibility and collaboration within a community. The thesis ends with a discussion about how the alternative futures could facilitate cross-level interaction and mobilisation of community members, and concludes in strategies for how rurban municipalities could develop into the future.
Keywords: Rurban, Collaboration, Valuemaking, Transformation